2017
DOI: 10.1016/j.nano.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size and pegylation of liposomes and peptide-based synthetic lipoproteins on tumor targeting

Abstract: Synthetic high-density lipoprotein nanoparticles (sHDL) are a valuable class of nanomedicines with established animal safety profile, clinical tolerability and therapeutic efficacy for cardiovascular applications. In this study we examined how the scavenger receptor B-I-mediated (SR-BI) tumor-targeting ability of sHDL, long plasma circulation half-life, and small particle size (9.6 ± 0.2 nm) impacted sHDL accumulation in SR-BI positive colorectal carcinoma cells, 3D tumor spheroids, and in vivo xenografts. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 56 publications
2
67
0
Order By: Relevance
“…Due to the negative effect of coating, PEGylation is applied as a replacement for increasing the stability and loading of the drug, as well as decreasing the size of particles. Moreover, PEG has a high biocompatibility . The current research describes the PEGylation process of characterization nanoliposomes loaded cisplatin to monitor the potency and efficacy of newly synthesized nanoliposome on the elimination of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the negative effect of coating, PEGylation is applied as a replacement for increasing the stability and loading of the drug, as well as decreasing the size of particles. Moreover, PEG has a high biocompatibility . The current research describes the PEGylation process of characterization nanoliposomes loaded cisplatin to monitor the potency and efficacy of newly synthesized nanoliposome on the elimination of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…As SR-BI is expressed by the cells, the rHDL could -in principle -be actively taken up by all cells in the spheroids, thus resulting in likewise decreased accumulation towards the tumor center due to enhanced clearance by the outermost cells, compared to similar sized non-targeting NPs. In contrast, Tang et al 29 suggest that SR-BI receptor-mediated cell uptake of HDL-mimicking NPs in the core of the tumor spheroid is important for enhanced penetration of the NPs. They based this claim on the observation that PEGylation of the HDL-mimicking NPs decreased the penetration into the tumor spheroid, which they attribute to SR-BI interactions being diminished by PEG.…”
Section: The Effect Of Np Design On the Penetration Efficiencymentioning
confidence: 90%
“…rapid proliferation at the surface and slow metabolism -or necrosis -in the center of spheroids 25 . The majority of studies of NP distributions in tumor spheroids use tumor spheroid fixation [26][27][28][29][30][31][32][33][34] , often in combination with histological sectioning 7,[35][36][37][38] . Nevertheless, there are also reports of NP penetration in live tumor spheroids using confocal-scanning microscopy [39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%
“…However, as apolipoproteins are generally obtained via extraction from animal plasma or recombinant expression systems, to apply apolipoprotein‐based lipid nanodisks to the living body, some issues pertaining to their safety and productivity, including cost, need to be addressed. Instead, chemically synthesized peptides are sometimes used as scaffolding molecules for lipid nanodisks . Recently, it has been shown that styrene maleic acid copolymer (SMA), which is known to be a biocompatible synthetic polymer, can produce lipid nanodisks (SMA nanodisks).…”
Section: Introductionmentioning
confidence: 99%